Advances in chilling injury of postharvest fruit and vegetable: Extracellular ATP aspects. Issue 5 (25th July 2022) - Shan, Youxia; Zhang, Dandan; Luo, Zisheng; Li, Taotao; Qu, Hongxia; Duan, Xuewu; Jiang, Yueming
Abstract: Due to the global use of cold chain, the development of postharvest technology to reduce chilling injury (CI) in postharvest fruits and vegetables during storage and transport is needed urgently. Considerable evidence shows that maintaining intracellular adenosine triphosphate (iATP) in harvested fruits and vegetables is beneficial to inhibiting CI occurrence. Extracellular ATP (eATP) is a damage‐associated signal molecule and plays an important role in CI of postharvest fruits and vegetables through its receptor and subsequent signal transduction under low‐temperature stress. The development of new aptasensors for the simultaneous determination of eATP level allows for better understanding of the roles of eATP in a myriad of responses mediated by low‐temperature stress in relation to the chilling tolerance of postharvest fruits and vegetables. The multiple biological functions of eATP and its receptors in postharvest fruits and vegetables were attributed to interactions with reactive oxygen species (ROS) and nitric oxide (NO) in coordination with phytohormones and other signaling molecules via downstream physiological activities. The complicated interconnection among eATP in relation to its receptors, eATP/iATP homeostasis, ROS, NO, and heat shock proteins triggered by eATP recognition has been emphasized. This paper reviews recent advances in the beneficial effects of energy handling, outlines the production and homeostasis of eATP, discusses the possible mechanism of eATP and its receptors in chilling tolerance, and provides future research directions for CI in postharvest fruits and vegetables during low‐temperature storage.